An Efficient algorithm for robot manipulators dynamic computation - Tenreiro Machado, J. A. (2019)
Despite recent advances in robot manipulator inversc dynamic computing methods, the development of industrial implementations of real-time controllers is still highly difficult, and impractical, due to the large mumber of arithmetic and transcendental floating point operations involved. The paper presents a method based on the use of a combination of boolean ond ordinary algebra that leads to a considerable reduction of the on-line computing time. Terms of the link torque equations are calculated by boolean algebra, using Binary Decision Diagrams, and are then combinated by arithmetiic summations. The result is an efficient computational technique for real-time robot manipulator nonlinear control which is well suited to today's digital technology. The method, which is not restricted to the particular application described in the paper, is well adapted to implementation on a parallel architecture with performance improvement porportional to the number of processors, and without scheduling problems.